CHALLENGES OF IMPLEMENTATION OF REGULATIONS ON PUBLIC PROPERTY IN SERBIA - Nikolić, Ljubica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The effectiveness of the disposal of public property is conditioned by: legal regulation and its application, the availability of information about public property, as well as the responsibility of the persons who decide on the disposal of public property. In this paper, we point out: regulations in Serbia in this area, the problem of law enforcement, as well as some examples from practice on the disposal of public property in Serbia, which, in our opinion, call into question the public interest. The law, its implementation and state policy in this area together determine the economic effects of the disposal of public property. Correct legal solutions and formally independent institutions that apply laws in the field of public property are not a guarantee of protection of the public interest, if there is a selective application of rights. On the other hand, the state, as a creator of rights, can abuse its opportunities and create regulations that allow it room for free action without responsibility and to the detriment of the general interest. The laws in the field of public property in Serbia provide a solid basis for the protection of public interest and the control of the disposal of public property. In practice, however, we come across: contracts by which the RS disposed of public property that are not publicly available; the non-transparency of this information and the limitation of competition between persons dealing with public property encourage corruption; suspicion of irregularity in numerous public procurements; passivity of institutions responsible for the protection of legality and public interest. In a word, the application of laws in the field of public property in Serbia is often associated with undermining the rule of law.